Effects of mecA and mecB (clpC) mutations on expression of sigD, which encodes an alternative sigma factor, and autolysin operons and on flagellin synthesis in Bacillus subtilis. - Rashid, M H (1996)
The expression of the major vegetative phase-specific autolysin genes (cwlB [lytC] and cwlG [lytD]) was greatly reduced by mecA and mecB null mutations. In contrast to the negative effects on late competence genes (such as comG) and levansucrase gene (sacB) expression, this positive effect of mec genes on autolysin gene expression was not mediated through the ComK protein but apparently through the level of the SigD protein. The pleiotropic effects of the mec mutations, i.e., the reduction of sigD expression and the overexpression of the ComK protein, seem not to be interwoven since the SigD- and ComK-dependent functions are clearly separable in the mec mutants. We also show that the synthesis of the flagellin protein, which is encoded by the SigD-dependent hag gene, was similarly affected by the mec mutations. Complementation analysis with a SigD-overproducing plasmid, pHYSigD, in mec mutants revealed the reversion of almost all of the SigD-dependent phenotypes except motility. This finding suggested that Mec proteins act on motility genes at two levels, one of which is apparently SigD independent. Finally, we discuss the transcriptional regulation of the sigD gene by multiple regulators, i.e., MecA, MecB, SinR (FlaD), and DegS-DegU, and its implications for cells in a global context.